Contamination of Coliform Bacteria on Ocimum basilicum at Traditional Markets, Jember Regency - Hanifah S Haq; Enny Suswati; Yudha Nurdian; Diana C Mufida; Angga M Raharjo (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
Basil is one type of vegetable that can be consumed without any processing. Unprocessed vegetables can cause contamination from Coliform bacteria. This study aimed to determine the number and identification of coliform fecal bacteria as a biological indicator suitable for consumption. This study used descriptive observational with a cross-sectional from November 2020 to March 2021. The research locations are from 8 Traditional Markets in Jember and the Microbiology Laboratory, Faculty of Medicine Jember University. The sample in this study consisted of 40 samples from basil vegetable sellers. The Most Probable Number method was carried out in two stages in this study. First, a presumptive test using lactose broth, and two, a complete test using Eosin Methylene Blue. The results of the presumptive test obtained 100% of the number of MPNs that exceeded the maximum limit for food quality suitable for consumption, according to BPOM. The complete test results showed that 82.5% of basil was contaminated with fecal coliform bacteria, namely Escherichia coli. Practically all the samples were highly infected with coliform bacteria. Suggestions the community is expected to pay attention to techniques in washing and processing basil vegetables properly to break the chain of bacterial contamination